The process of “capacity building” in the public administration: artificial intelligence, transparency and new models of the administrative decision - Luise, Gianluca; Cocozza, Giovanni (Frontiers in Political Science, 2025)
This paper explores the evolving role of AI in administrative empowerment, analyzing its implications for public administration and legal norms in Italy and the broader European context. It examines key institutional and legislative developments and the broader impact of AI on administrative law, aiming to provide a comprehensive understanding of how emerging technologies are shaping modern governance structures. Through this analysis, the study contributes to the ongoing discourse on AI regulation, emphasizing the need for a harmonized approach that fosters both technological progress and legal integrity.